THE IMPORTANCE AND PERFORMANCE ANALYSIS OF AGENT COMPETENCIES (Case Study: PT. Prudential Life Assurance) - Oroh, Cliff R.; Kindangen, Paulus P.; Tielung, Maria V. J. (FEB Universitas Sam Ratulangi Manado, 2017)
Abstract: The success of the Lifeâ€™s Insurance Company is influenced by the performance of the sales agents inside. Based on the previous related research about the agent competencies, researcher determine the most important five attributes in agent competencies to measuring the customers satisfaction to their performance, namely: Performance (Reliability), Cooperation (Credibility), Guarantee (Security), Personal Skill (Ability), and Experience. (1) Personal Skill (Ability) is located in the quadrant I â€œConcentrate Hereâ€ (very important to employees, but performance levels are fairly low); (2) Guarantee (security) and Cooperation (Credibility) are located in quadrant II â€œKeep up the good workâ€ (very important to employees, and at the same time has a high level of performance in these activities); and (3) Experience and Performance (Reliability) is located in the quadrant III â€œLow priorityâ€ (low importance and low performance). Keywords: Importance Performance Analysis, Agent Competencies, Personal Skill (Ability), Guarantee (Security), Cooperation (Credibility), Experience, Performance (Reliability).